Speaking Activities In English Textbook For Junior High School Grade Vii Oncognitive Domains - Ritonga, Malia Anjani (Universitas Muhammadiyah Sumatera Utara, 2021)
This research deals with the cognitive domains on speaking activities in English textbook of Junior High School grade VII. It was intended to investigate the categories and processes of cognitive domains applied on speaking activity in the English textbook. The method used in this study was descriptive qualitative method. The data were gained from speaking activities written in the English textbook entitled When English Rings a Bell published by PusatKurikulumdanPerbukuan, Balitbang, Kemdikbud. There were 48 data of speaking activities taken from the English textbook. The data collected were analyzed based on Miles and Hubermann analysis model, including data reduction, data display, and conclusion. So, it was concluded that not all categories of cognitive domains were found on speaking activities in the English textbook and those were not realized into the whole processes of speaking activity. Thus, the English textbook for seventh-grade Junior High School entitled When English Rings a Bell was not good enough in terms of cognitive domain distributions and speaking activities variations. In addition, although the textbook did not include all cognitive domains, it was still categorized as high order thinking skill-textbook criteria because creating as one level of cognitive represent the criteria.